HAV Infection Associated with Hemophagocytic Syndrome - H. Aamri; R. Elqadiry; H. Nassih; A. Bourrahouat; I. Ait Sab (Case Reports in Infectious Diseases)
Hemophagocytic syndrome is a rare disease that can cause severe illness and death. This condition is caused by the presence of antibodies against the hepatitis A virus. A positive anti-IGM antibody was identified in our 7-year-old patient with severe hepatitis A. A week after the hepatitis A was diagnosed, the patient experienced pancytopenia, which was worsened by prolonged fever. He was then diagnosed with macrophage activation syndrome. The treatment with steroids improved the clinical and biological evolution of the condition.